Thyroid hormone action in adult neurogliogenic niches: the known and unknown - Valcárcel-Hernández, Victor; Mayerl, Steffen; Guadaño-Ferraz, Ana; Remaud, Sylvie (Frontiers in Endocrinology, 2024)
Over the last decades, thyroid hormones (THs) signaling has been established as a key signaling cue for the proper maintenance of brain functions in adult mammals, including humans. One of the most fascinating roles of THs in the mature mammalian brain is their ability to regulate adult neurogliogenic processes. In this respect, THs control the generation of new neuronal and glial progenitors from neural stem cells (NSCs) as well as their final differentiation and maturation programs. In this review, we summarize current knowledge on the cellular organization of adult rodent neurogliogenic niches encompassing well-established niches in the subventricular zone (SVZ) lining the lateral ventricles, the hippocampal subgranular zone (SGZ), and the hypothalamus, but also less characterized niches in the striatum and the cerebral cortex. We then discuss critical questions regarding how THs availability is regulated in the respective niches in rodents and larger mammals as well as how modulating THs availability in those niches interferes with lineage decision and progression at the molecular, cellular, and functional levels. Based on those alterations, we explore the novel therapeutic avenues aiming at harnessing THs regulatory influences on neurogliogenic output to stimulate repair processes by influencing the generation of either new neurons (i.e. Alzheimer’s, Parkinson’s diseases), oligodendrocytes (multiple sclerosis) or both (stroke). Finally, we point out future challenges, which will shape research in this exciting field in the upcoming years.